IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS PESANTREN DI MA PONDOK PESANTREN AL-HASANAH KABUPATEN BENGKULU TENGAH - Yeyen Mardanita (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2018)
This research  is motivated because of the increasing  number of people’s negative  behaviors that occur in everyday life, especially among  school-age children such as drug use, sexual harassment, aggressive behavior, fights, bullying, deteriora- tion of religious tolerance  and  others.These negative  behaviors are a sign that Indonesia is on the brink of collapse.It takes an education that can change  the bad behavior for the better.Pondok Pesantren Al-Hasanah is an educational institution in which prioritize the formation  of the personality  and  mental  attitude  of learners  so that it has a good character and  become the next generation of brilliant nation  by instilling religious values  and  religious character.Based on  the  above  background, then  the formulation of the problem  in this research  is how the implementation of character-based pesantren education in MA Pondok Pesantren Al-Hasanah, what  is the method of character education in Al-Hasanah Islamic Boarding  School  and  what  are the factors inhibiting and supporting the implementation of character education based on boarding school At MA Pondok Pesantren Al-Hasanah.This study aims to determine the implementation of character-based education boarding school in MA Pondok Pe- santren  Al-Hasanah, to find out the method of character education based  boarding school in MA Pondok Pesantren Al-Hasanah and to determine the factors inhibiting and supporting the implementation of character education based  boarding school in MA Pondok Pesantren Al-Hasanah.This study is a qualitative  research  (qualitative  research).Data collection is done  by using obser- vation,  interview, and  documentation.With data  collection steps, data  reduction, data  presentation, and  conclusion.Based on the results of data analysis yag has been collected can be concluded that the implementation of character education in boarding school is applied  in several  values of character investing,  among  others:  religious values,  the value  of independence and  the value  of responsibility.Character education method in boarding school  Al-Hasanah implemented through  several  methods, namely:  exemplary  methods, methods of advice,  methods of habituation, and  the method of memorization.Factors inhibiting and supporting the implementation of character education based  on boarding school in Pondok Pesantren Al-Hasanah Central Bengkulu Regency, among  others:Not  yet optimal sources of operational funds and constraints  of the individual students  them- selves, such as easily bored  and undisciplined.While the supporting factors, among  others, the existence of a sincere soul of the caregivers and ustadz / ustadzah and the existence  of a dormitory  system or accommodation for the santri